Expression of c-series gangliosides in rat hepatocytes and liver tissues - Saito, Megumi; Sugiyama, Kiyoshi (Biochimica et Biophysica Acta (BBA) - General Subjects, 1999)
C-series gangliosides in rat hepatocytes and liver tissues were analyzed by thin-layer chromatographic (TLC) immunostaining with the specific monoclonal antibody A2B5. Primary cultures of hepatocytes isolated from adult rats were immunostained positively by A2B5. TLC immunostaining with A2B5 of gangliosides from the cells suggested that rat hepatocytes express c-series gangliosides including GT3, GT1c, GQ1c, and GP1c. Expression of c-series gangliosides in cultured hepatocytes was modulated by growth conditions of cells. The amount of GT3 was increased significantly by epidermal growth factor, while the contents of polysialo species such as GT1c, GQ1c, and GP1c were enhanced by higher cell density in culture. Examination of c-series gangliosides in rat liver tissues showed a unique developmental profile with a shift from GT3-dominant to polysialo species-dominant composition in late embryonic stages. These results suggest that the expression of c-series gangliosides in rat hepatocytes is regulated in a growth- and development-dependent manner.